Preparation method of paper cloth composite base abrasive belt joint

CN122956375APending Publication Date: 2026-10-23SHAOGUAN WEIMING ABRASIVE MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611056423.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,由于纸层与布层在结构、厚度、吸胶性和去除特性方面存在差异,采用常规磨边搭接时,容易出现层厚叠加不均、纸纤维剥离、布纤维起毛、端缘翘起及接头刚度过高等问题;采用背面衬片对接时,则会增加附加材料和粘接界面,难以充分利用纸布复合基本身的层状结构

Benefits of technology

本发明分别从两个待接合端部的砂面侧和背面侧进行互补去层,利用纸布复合基自身的布层和纸层形成第一接合部和第二接合部,并结合接头胶厚度补偿、砂面磨削功能层端缘对接及压合固化,实现了接头区层序重构、厚度匹配和界面可靠粘接,满足高线速、高负荷以及对磨削表面质量要求较高的工况要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122956375A_ABST
    Figure CN122956375A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a paper-cloth composite base abrasive belt joint and relates to the technical field of annular abrasive belts. The method comprises the following steps: respectively performing complementary delamination treatment on two to-be-connected end portions of a paper-cloth composite base abrasive belt from the sand surface side and the back surface side, forming a first joint portion of an exposed paper layer at the first end portion, forming a second joint portion of an exposed cloth layer at the second end portion, and performing joint surface grinding function layer end edge butt joint, joint adhesive layer thickness compensation, interface adjustment and press consolidation. The method realizes layer sequence reconstruction, thickness matching and interface strengthening of the joint area, and has the application prospect in annular abrasive belt products with high linear speed, high load and high requirements for the grinding surface quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of annular abrasive belt technology, and more particularly to a method for preparing a paper-cloth composite abrasive belt joint. Background Technology

[0002] Annular abrasive belts are typically formed by cutting a rolled coated abrasive and joining two free ends. Existing abrasive belt joints mainly include lap joints and butt-joint joints. Lap joints, achieved by grinding the ends and then bonding them together, are prone to localized thickening and abrupt changes in stiffness due to the overlapping of the base layer and adhesive layer. This can lead to periodic impacts, vibration marks, and joint wear marks during high-speed abrasive belt operation. Butt-joint joints, reinforced by attaching fabric or film backing across the seam on the back of the abrasive belt, reduce overlap of the abrasive surface. However, thickness differences and stress concentrations can still occur at the edge of the backing and the boundary of the adhesive layer, making them susceptible to fatigue peeling under repeated bending or humid and hot conditions.

[0003] Paper-cloth composite substrates consist of paper layers, composite adhesive layers, and cloth layers, combining the smoothness and rigidity of paper layers with the tensile strength, tear resistance, and flexural strength of cloth layers. However, due to differences in structure, thickness, adhesive absorption, and removal characteristics between the paper and cloth layers, conventional edge grinding and overlapping can easily lead to problems such as uneven layer thickness, paper fiber peeling, cloth fiber fuzzing, edge lifting, and excessive joint stiffness. Using backing sheets for butt joints increases the amount of additional material and the bonding interface, making it difficult to fully utilize the layered structure of the paper-cloth composite substrate itself. Furthermore, if the abrasive grinding functional layers at both ends of the abrasive belt overlap or have excessive gaps, it can cause discontinuity in the abrasive surface height or grinding action, affecting the surface quality of the workpiece.

[0004] Therefore, there is a need for a paper-cloth composite substrate sand belt joint preparation method that can reduce the thickness difference and stiffness change of the joint while ensuring the bonding strength and flexural resistance of the joint, and improve the continuity of the sand surface and the interface stability under humid and hot conditions. Summary of the Invention

[0005] The present invention discloses a method for preparing a paper-cloth composite abrasive belt connector, comprising a top-coated layer, an abrasive layer, a base adhesive layer, a cloth layer, a primary composite adhesive layer, and a paper layer disposed from the abrasive surface side to the back side, wherein the top-coated layer is an upper adhesive layer covering the surface of the abrasive particles and the gaps between the particles in the abrasive layer. The preparation method includes the following steps: S1. Cut the two ends of the paper-cloth composite sand belt blank to be joined into the first end and the second end; S2. Remove the sanding functional layer, the cloth layer, and at least part of the original composite adhesive layer from the sanding side of the first end; wherein the sanding functional layer includes a composite adhesive layer, an abrasive layer, and a base adhesive layer, so that the paper layer is exposed and forms a first joint. S3. Remove the paper layer and at least part of the original composite adhesive layer from the back side of the second end along the joint length direction, so that the cloth layer is exposed and a second joint is formed. The second joint retains the composite adhesive layer, abrasive layer, base adhesive layer and cloth layer on its sanding side. S4. Apply joint adhesive to the first joint and / or the second joint, stack the second joint on the first joint, so that the cloth layer at the second end overlaps with the paper layer at the first end, and make the abrasive grinding functional layer edge of the first end and the second end align with each other, wherein the absolute value of the gap or overlap between the abrasive layer edge is ≤0.10mm. S5. Press the overlapping parts together to cure the joint adhesive and obtain an annular sand belt.

[0006] The sum of the thickness of the retained paper layer at the first joint, the thickness of the retained cloth layer at the second joint, and the thickness of the cured joint adhesive layer satisfies the following formula: Among them, t 布 To maintain the compacted thickness of the fabric layer at the first joint, t 纸 To retain the compacted thickness of the paper layer at the second joint, t 胶 The thickness of the adhesive layer for the cured joint is defined as follows: H0 is the measured thickness of the paper-cloth composite substrate in the non-joint area, and ΔH is the allowable thickness deviation, ΔH≤0.08 mm, more preferably ≤0.05 mm.

[0007] Preferably, the angle between the joint line of the first end and the second end and the running direction of the sanding belt is 45°~80°, and the overlap length of the first joint and the second joint along the length direction of the sanding belt is 8~25 mm respectively.

[0008] Preferably, a gradual transition section with a length of 1 to 5 mm is formed between the first joint and the first end non-joint area, and between the second joint and the second end non-joint area; the residual height of the cloth fiber on the surface of the first joint is ≤0.05 mm, and the residual thickness of the paper layer on the surface of the second joint is ≤0.03 mm.

[0009] Preferably, the distance between the two abrasive grinding functional layer end edges measured along the abrasive belt running direction, i.e. the abrasive surface mating tolerance, has an absolute value ≤ 0.10 mm. The abrasive surface mating tolerance takes a positive value when there is a gap and a negative value when there is local overlap. More preferably, it is a micro gap of 0~0.08 mm to avoid abrasive layer stacking.

[0010] Preferably, the total thickness of the paper-cloth composite substrate is 0.78~0.92 mm, the thickness of the cloth layer is 0.40~0.55 mm, and the thickness of the paper layer is 0.28~0.40 mm; more preferably, the total thickness of the paper-cloth composite substrate is 0.85 mm, the thickness of the cloth layer is 0.50 mm, and the thickness of the paper layer is 0.35 mm.

[0011] Preferably, before applying the joint adhesive, an interface conditioning liquid is applied to the exposed paper layer of the first joint; the interface conditioning liquid comprises, by effective solid mass parts: 100 parts of waterborne polyurethane, 2-5 parts of water-dispersible carbodiimide, 0.3-1.2 parts of aminosilane and 0.1-0.5 parts of nonionic wetting agent, and adjusted with water to a solid content of 8%-18%.

[0012] Preferably, based on effective solids by weight, the joint adhesive comprises: 100 parts of hydroxyl-type waterborne polyurethane, 15-35 parts of carboxylated nitrile latex, 8-20 parts of waterborne epoxy resin, 4-10 parts of water-dispersible polyisocyanate, 0.3-1.5 parts of epoxy silane, 0.2-1.5 parts of silica, 0.05-0.5 parts of silicone defoamer, and 0.05-0.8 parts of rheology modifier.

[0013] Preferably, the dry coating amount of the interface conditioning liquid is 2~8 g / m³. 2 The dry coating amount of the joint adhesive is 35~75g / m. 2 The pressing temperature is 90~125℃, the pressing pressure is 0.30~0.80 MPa, and the holding time is 60~240 s.

[0014] Preferably, after pressing, the material is post-cured for 12 to 36 hours in an environment of 20 to 30°C and 40% to 65% relative humidity, and an edge sealant with a solid content of 15% to 30% is applied on both sides of the abrasive layer joint within a range of 0.5 to 1.5 mm.

[0015] Preferably, the thickness of the retained paper layer of the first joint and the thickness of the retained cloth layer of the second joint are measured before pressing, and the target cured joint adhesive layer thickness is calculated based on the thickness of the non-joint area; when it exceeds 0.02~0.08 mm, the first joint and / or the second joint are further calibrated by grinding.

[0016] Compared with the prior art, the beneficial technical effects of the present invention are as follows: This invention performs complementary delamination from the sanded surface side and the back side of the two ends to be joined, respectively, and uses the cloth layer and paper layer of the paper-cloth composite substrate to form the first joint and the second joint. Combined with the joint adhesive thickness compensation, the end edge docking of the sanded surface grinding functional layer and the pressing and curing, the layer sequence reconstruction, thickness matching and reliable interface bonding of the joint area are realized, which meets the working conditions of high linear speed, high load and high requirements for grinding surface quality.

[0017] This invention utilizes the overlapping of paper and cloth layers in the original paper-cloth composite matrix, eliminating the need for independent reinforcing linings spanning the seams. This reduces stress concentration and abrupt stiffness changes caused by additional material interfaces and lining edge variations. By controlling the total thickness of the retained cloth layer, retained paper layer, and cured joint adhesive layer to match the thickness of the non-joint area, the thickness difference in the joint area is reduced, thereby minimizing periodic impacts and joint wear marks during belt abrasion.

[0018] This invention connects the abrasive layer edges at both ends to avoid overlapping of the adhesive layer, abrasive layer and base adhesive layer in the overlap area. By limiting the gap or overlap at the edges, it improves the sanding height and the continuity of grinding action. A gradual transition section is set at the root of the joint, and the amount of paper layer and cloth fiber residue is controlled to mitigate cross-sectional changes and reduce fiber peeling and edge stress concentration.

[0019] This invention improves the uniformity of adhesive absorption in the paper layer and the bonding strength between the paper layer, fabric layer, and joint adhesive by adjusting the interface of the exposed paper layer and combining it with quantitative glue application, calibrated grinding, and hot pressing curing. This enhances the joint's resistance to damp heat, flexural strength, and service life. The method can be implemented using double-sided edge grinding, quantitative glue application, and hot pressing equipment. The process parameters are easy to measure and control, making it suitable for continuous and mass production. Attached Figure Description

[0020] The present invention will be further described below with reference to the accompanying drawings.

[0021] Figure 1 This is a cross-sectional schematic diagram of the non-joint area of ​​the paper-cloth composite base sand belt used in this invention; Figure 2 A schematic cross-sectional view of the complementary embedded overlapping area; Figure 3 This is a schematic diagram showing the mating state of the sand-faced side; Figure 4 This is a schematic diagram showing the overlapping state of the back side paper fabric.

[0022] Explanation of reference numerals in the attached drawings: 1-Abrasive layer; 2-Paper layer; 3-Original composite adhesive layer; 4-Fabric layer; 5-First end; 6-Second end; 7-First joint; 8-Second joint; 9-Joint adhesive layer; 10-Abrasive layer butt joint; 11-Gradual transition section; 12-Complementary embedded overlapping area; 13-Layer adhesive layer; 14-Base adhesive layer. Detailed Implementation

[0023] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0024] 1. Raw materials and structure The paper-cloth composite abrasive belt blank, from the abrasive surface to the back, comprises, in sequence, an adhesive layer 13, an abrasive layer 1, a base adhesive layer 14, a cloth layer 4, the original composite adhesive layer 3, and a paper layer 2. The adhesive layer 13 is an upper adhesive layer covering the outside of the abrasive layer 1, used to coat the abrasive particles and the gaps between them with adhesive. The base adhesive layer 14 is used to bond the abrasive layer 1 to the cloth layer 4. The abrasive layer 1 is an abrasive grain layer, and the abrasive grains can be brown fused alumina, white fused alumina, zirconium fused alumina, ceramic alumina, silicon carbide, or a combination thereof. The paper layer is water-resistant paper or impregnated paper, and the cloth layer is cotton cloth, polyester-cotton cloth, polyester cloth, or polyamide cloth. The thickness of each paper and cloth layer can be measured before lamination or according to their respective standard conditions; after lamination, due to compression and adhesive penetration, the overall measured thickness may be less than the simple sum of the thicknesses of each individual layer.

[0025] 2. Connector preparation steps 1) Cutting: Cut the abrasive belt blank according to the target circumference, and cut the two free ends into bevels in the same direction. The angle β between the joint line and the running direction is 60°~72°. The narrower the abrasive belt, the smaller β can be to increase the joint line length. 2) First end sanding edge: Use a diamond grinding wheel to remove the composite adhesive layer, abrasive layer and base adhesive layer in the first end joint area, and then use a belt grinding head or precision milling head to continue removing the cloth layer and the original composite adhesive layer until the paper layer is continuously exposed to form the first joint 7, and control the height of the residual cloth fiber ≤0.05 mm; a 1~5 mm gradual transition section 11 is formed at the root of the joint; 3) Grinding the back side of the second end: Remove the paper layer and the original composite adhesive layer from the back side of the second end joint area until the cloth layer is continuously exposed to form the second joint 8; the second joint retains the abrasive layer above the cloth layer, the paper layer removal depth is 0.35 mm, and the residual thickness of the paper layer is controlled to be ≤0.03 mm. 4) Cleaning and calibration: Clean the grinding debris with oil-free compressed air and vacuum; if necessary, wipe and dry with an aqueous solution containing no more than 30% isopropanol; measure t paper, t cloth and H0, and calibrate the grinding amount according to the target adhesive layer thickness. The surface roughness Ra of the first joint and the second joint is 5~30 μm. 5) Interface treatment and adhesive application: Preferably, a low-viscosity interface conditioning liquid is applied only to the exposed paper layer of the first joint, allowing it to penetrate 10% to 50% of the paper layer thickness without penetrating through; after pre-drying, a joint adhesive is applied quantitatively to the joint surface of the paper layer and / or cloth layer. 6) Alignment and hot pressing: The second joint 8 is stacked on the first joint 7 to bond the cloth layer 4 to the paper layer 2. A limiting fixture is used to adjust the edge of the abrasive grinding functional layer to control the abrasive surface mating tolerance of the butt joint within ±0.10 mm; after covering with a heat-resistant release film, it is pressed at 90~125℃ and 0.30~0.80 MPa for 60~240 s. 7) Post-curing and finishing: Place at 20~30℃ and relative humidity 40%~65% for 12~36 hours, remove excess glue and lightly grind the joint protrusions; a narrow strip of sealing glue can be applied to both sides of the joint, and finally measure the thickness of the joint area and the mating error of the sand face.

[0026] 3. Adhesive system In some specific embodiments of the present invention, the preferred formulation of the interface conditioning liquid is shown in the table below. Its function is to reduce the difference in adhesive absorption on the paper surface, lock in loose fibers, and provide a continuous reaction interface for the joint adhesive.

[0027] The hydroxyl-type aqueous polyurethane dispersion is Dispercoll. ® U 42、Dispercoll ® U 54, Bayhydrol ® U 2757, Vesmody ® U901, Vesmody ® U906; the water-dispersible carbodiimide is Carbodilite. TM V-02-L2, Carbodilite TM SV-02, Picassian ® XL-701, Picassian ® XL-702; the nonionic wetting agent is PEG-400.

[0028] During preparation, waterborne polyurethane is stirred at 300~500 r / min, and carbodiimide, silane and wetting agent are added in sequence. Finally, water is added to adjust the solid content. It should be used within 8 hours after preparation.

[0029] In some specific embodiments of the present invention, the preferred formulation of the joint adhesive is shown in the table below: the polyisocyanate should be added before use, and the pot life after mixing is 2-6 hours.

[0030] The hydroxyl-type aqueous polyurethane dispersion is Dispercoll. ® U 42、Dispercoll ® U 54, Bayhydrol ®U 2757, Vesmody ® U901, Vesmody ® U906; the carboxylated nitrile butadiene latex is Nipol ® LX430, Nipol ® 1571H, Synthomer 6322, or Synthomer 6311; the water-dispersible aliphatic polyisocyanate is Bayhydur. ® 304, Bayhydur ® 3100, Bayhydur ® XP 2655, Aquolin ® 268 or Aquolin ® 278; The hydrophilic fumed silica is AEROSIL. ® 200, AEROSIL ® 380 or CAB-O-SIL ® M-5; the associative thickener is Coapur. TM XS 71.

[0031] When preparing the joint adhesive, first mix polyurethane, nitrile latex, and epoxy resin, then add silica dispersion, silane, silicone defoamer, and thickener; add polyisocyanate before coating and mix at low speed. The application viscosity of the joint adhesive at 25°C is 1500~5000 mPa·s.

[0032] Example 1: A paper-cloth composite abrasive belt connector includes a top adhesive layer 13, an abrasive layer 1, a base adhesive layer 14, a cloth layer 4, a base composite adhesive layer 3, and a paper layer 2, arranged from the abrasive surface side to the back side. The preparation method of the paper-cloth composite abrasive belt connector is as follows: The P120 brown corundum paper-cloth composite abrasive belt blank is used, with a finished product size of 75 mm × 2000 mm. The measured thickness H0 of the composite base in the non-joint area is 0.85 ± 0.02 mm; the cloth layer thickness is 0.50 mm, and the paper layer thickness is 0.35 mm. Both ends are cut into bevels with a joint line at a 67° angle to the running direction, and the overlap length is 14 mm.

[0033] The first end 5 removes the top layer, abrasive layer, base layer, cloth layer, and original composite adhesive layer sequentially from the sand surface side, forming a paper layer joint. The remaining cloth fiber height is 0.03 mm, and the transition section length is 3 mm. The second end 6 removes 0.35 mm of paper layer and the original composite adhesive layer from the back side, forming a cloth layer joint retaining the top layer, abrasive layer, base layer, and cloth layer. The remaining paper layer thickness is 0.02 mm, and the transition section length is 3 mm. The Ra of the two joint surfaces is 15 μm.

[0034] Interface conditioning fluid: Based on effective solids mass, hydroxyl-type aqueous polyurethane dispersion Dispercoll ® U 54100 parts, water-dispersible carbodilite TM SV-02 4 parts, γ-aminopropyltriethoxysilane (KH-550) 0.8 parts, nonionic wetting agent PEG-400 0.3 parts, and deionized water adjusted to a solid content of 12%; during preparation, the waterborne polyurethane is stirred at 450 r / min, and carbodiimide, silane and wetting agent are added in sequence, and finally water is added to adjust the solid content. It should be prepared fresh for use.

[0035] Joint adhesive: hydroxyl-based waterborne polyurethane dispersion Dispercoll, based on effective solids parts by weight. ® U 54 100 parts, carboxylated nitrile butadiene latex Nipol ® 25 parts LX430, 12 parts waterborne bisphenol A epoxy resin, and water-dispersible aliphatic polyisocyanate Bayhydur ® 304 (7 parts), γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) (0.8 parts), hydrophilic fumed silica AEROSIL ® 200 0.8 parts, silicone defoamer 0.2 parts, associative thickener Coapur TM XS 71 0.3 parts, adjusted to a solid content of 48% with deionized water. When preparing the joint adhesive, first mix polyurethane, nitrile latex and epoxy resin, then add silica dispersion, silane, silicone defoamer and thickener; add polyisocyanate before coating and mix at low speed, prepare fresh for use.

[0036] The interface conditioning liquid is applied only to the exposed paper layer of the first joint 7, with a dry coating weight of 5 g / m². 2 Pre-dry at 60℃ for 2 min; apply joint adhesive to the bonding surface of the paper and cloth layers, with a total dry coating weight of 52 g / m. 2 The second joint 8 is stacked on top of the first joint 7, with the gap between the abrasive layer edges controlled at 0.03 mm. It is then hot-pressed at 105℃ and 0.55 MPa for 120 s. Subsequently, it is post-cured at 23±2℃ and 50%±5% relative humidity for 24 h, and the edges on both sides of the joint are sealed with a 1 mm range of joint adhesive diluted with 20% solids content.

[0037] Example 2 The difference from Example 1 is that: the angle between the joint line and the running direction is 60°, the overlap length is 18 mm, the length of the gradual transition section 11 of the first end 5 and the second end 6 is 4 mm, and the dry coating amount of the joint adhesive is 48 g / m. 2 The hot pressing conditions were 100℃, 0.60 MPa, and 150 s.

[0038] Example 3 The difference from Example 1 is that the solid content of the interface conditioning liquid is 10%, and the dry coating amount is 4 g / m. 2 The joint adhesive contains 30 parts carboxylated nitrile latex, 8 parts waterborne epoxy resin, and 8 parts water-dispersible polyisocyanate. The dry coating weight of the joint adhesive is 55 g / m². 2 .

[0039] Example 4 The difference from Example 1 is that: P80 zirconium corundum paper-cloth composite base sand belt is used, the finished product size is 100 mm × 2500 mm, the actual thickness of the composite base in the non-joint area is 0.90 ± 0.02 mm; the cloth layer thickness is 0.52 mm, the paper layer thickness is 0.38 mm; the overlap length is 16 mm, and the hot pressing pressure is 0.65 MPa.

[0040] Example 5 The difference from Example 1 is that the sandblasted surface gap is controlled at 0.08 mm, and the dry coating amount of the joint adhesive is 45 g / m. 2 The hot-pressing conditions were 95℃, 0.50 MPa, and 210 s, with a post-curing time of 36 h.

[0041] Example 6 The difference from Example 1 is that the overlap length is 10 mm, the residual thickness of the paper layer at the first end 5 is 0.03 mm, the residual fabric fiber height at the second end 6 is 0.05 mm, and the dry coating amount of the joint adhesive is 62 g / m. 2 The hot pressing conditions were 115℃, 0.45MPa, and 90 s.

[0042] Comparative Example 1 The difference from Example 1 is that: at the first end, only the sanding functional layer and paper layer on the sanded side are ground off, without removing the original composite adhesive layer, and the cloth layer is not exposed; at the second end, only the adhesive layer on the back side is ground off, without removing the cloth layer, and the sanding functional layer on the sanded side is retained. All other process parameters are exactly the same as in Example 1.

[0043] Comparative Example 2 Using the same blank as in Example 1, the two ends are directly butted together, and a 0.10 mm thick polyester fiber reinforced joint tape is pasted across the seam on the back; the sanding gap is 0.05 mm.

[0044] Comparative Example 3 The complementary embedded lap joint structure of Example 1 is adopted, but without thickness compensation, and the dry coating amount of the joint adhesive is increased to 120 g / m. 2 This results in a cured adhesive layer thickness of 0.15 mm.

[0045] Comparative Example 4 The complementary embedded overlapping structure of Example 1 is adopted, but the interface conditioning liquid is omitted, and the other conditions remain unchanged.

[0046] Comparative Example 5 The complementary embedded overlapping structure of Example 1 is adopted, but the gap between the two abrasive layer edges is controlled to 0.30 mm, while the other conditions remain unchanged.

[0047] Detection method: Joint thickness difference: Using a digital thickness gauge with a resolution of 0.001 mm, measure 10 points evenly along the width direction in the joint area, and measure 10 points in the adjacent non-joint area; take the absolute value of the difference between the average thickness of the two areas.

[0048] Joint tensile strength: Referring to the test method for tensile strength of coated abrasive, the specimen containing the joint is cut into 25 mm wide pieces, with the joint located in the middle of the fixture, the gauge length is 100 mm, the tensile speed is 100 mm / min, and the maximum load is recorded in N / 25 mm.

[0049] Moist heat strength retention rate: The tensile strength of the sample was measured after being placed at 70℃ and 90% relative humidity for 168 h and then restored to the standard environment for 2 h. The result was expressed as the ratio of the strength after moist heat to the initial strength.

[0050] Bending life: Install the annular abrasive belt on a double roller test device with diameters of 30 mm and 80 mm, with a linear speed of 20 m / s and a tension of 150 N, and run continuously until delamination or breakage with a length greater than 2 mm occurs at the joint, and record the number of cycles.

[0051] Joint cycle peak-valley difference: Grinding a 6061 aluminum alloy plate for 60s at a linear speed of 20 m / s and a contact pressure of 0.15 MPa, the surface peak-valley difference caused by the joint cycle is measured along the running direction of the abrasive belt.

[0052] Dynamic grinding life: Continuous grinding with the same equipment and load until the joint fails or the amount of material removed per unit time drops to 70% of the initial value, and the time is recorded.

[0053] Test results Table 1. Geometric and mechanical properties of the joints (mean ± standard deviation, n=5)

[0054] Table 2. Flexibility and grinding properties (mean ± standard deviation, n=5)

[0055] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A method for preparing a paper-cloth composite abrasive belt joint, characterized in that, The paper-cloth composite abrasive belt includes a backing layer (13), an abrasive layer (1), a base adhesive layer (14), a cloth layer (4), the original composite adhesive layer (3), and a paper layer (2) arranged from the abrasive surface side to the back side. The backing layer (13) is applied over the abrasive layer (1) and covers the surface of the abrasive particles and the gaps between the particles. The preparation method includes the following steps: S1. Cut the two ends of the paper-cloth composite base sand belt blank to be joined into the first end (5) and the second end (6). S2. Remove the sanding function layer, cloth layer (4) and at least part of the original composite adhesive layer (3) from the sanding side of the first end (5); wherein the sanding function layer includes a composite adhesive layer (13), an abrasive layer (1) and a base adhesive layer (14), so that the paper layer (2) is exposed and forms a first joint (7). S3. Remove the paper layer (2) and at least part of the original composite adhesive layer (3) from the back side of the second end (6) along the joint length direction, so that the cloth layer (4) is exposed and a second joint (8) is formed. The second joint (8) retains the composite adhesive layer (13), abrasive layer (1), base adhesive layer (14) and cloth layer (4) on its sand surface side. S4. Apply joint adhesive to the first joint (7) and / or the second joint (8), stack the second joint (8) on the first joint (7), so that the cloth layer (4) of the second end (6) overlaps with the paper layer (2) of the first end (5), and make the sanding function layer end edges of the first end (5) and the second end (6) abut against each other, and the absolute value of the gap or overlap between the end edges of the abrasive layer (1) is ≤0.10 mm; S5. Press the overlapping parts together to cure the joint adhesive and obtain an annular sanding belt; By calibrating and grinding the first joint (7) and / or the second joint (8) and controlling the dry coating amount of the joint adhesive, the sum of the thickness of the paper layer (2) retained in the first joint (7), the thickness of the cloth layer (4) retained in the second joint (8) and the thickness of the cured joint adhesive layer (9) is ≤0.05 mm relative to the measured thickness of the paper-cloth composite substrate in the non-joint area, and the maximum thickness difference between the joint area and the adjacent non-joint area after curing is ≤0.08 mm.

2. The method for preparing a paper-cloth composite abrasive belt joint according to claim 1, characterized in that, The angle between the joint line of the first end (5) and the second end (6) and the running direction of the sanding belt is 45°~80°, and the overlap length of the first joint (7) and the second joint (8) along the length of the sanding belt is 8~25 mm respectively.

3. The method for preparing a paper-cloth composite abrasive belt joint according to claim 1, characterized in that, A gradual transition section (11) with a length of 1~5 mm is formed between the first joint (7) and the non-joint area of ​​the first end (5) and between the second joint (8) and the non-joint area of ​​the second end (6); the residual height of the cloth fiber on the surface of the first joint (7) is ≤0.05 mm and the residual thickness of the paper layer on the surface of the second joint (8) is ≤0.03 mm.

4. The method for preparing a paper-cloth composite abrasive belt joint according to claim 1, characterized in that, The gap between the edges of the abrasive layer (1) is a micro-gap of 0~0.08 mm.

5. The method for preparing a paper-cloth composite abrasive belt joint according to claim 1, characterized in that, The total thickness of the paper-cloth composite substrate is 0.78~0.92 mm, the thickness of the cloth layer (4) is 0.40~0.55 mm, and the thickness of the paper layer (2) is 0.28~0.40 mm.

6. The method for preparing a paper-cloth composite abrasive belt joint according to claim 5, characterized in that, The total thickness of the paper-cloth composite substrate is 0.85 mm, the thickness of the cloth layer (4) is 0.50 mm, and the thickness of the paper layer (2) is 0.35 mm.

7. The method for preparing a paper-cloth composite abrasive belt joint according to claim 1, characterized in that, Before applying the joint adhesive, an interface conditioning liquid is applied to the exposed paper layer (2) of the first joint (7); Based on the effective solids mass, the interface conditioning liquid comprises: 100 parts of waterborne polyurethane, 2-5 parts of water-dispersible carbodiimide, 0.3-1.2 parts of aminosilane, and 0.1-0.5 parts of nonionic wetting agent, and is adjusted with water to a solids content of 8%-18%.

8. The method for preparing a paper-cloth composite abrasive belt joint according to claim 1, characterized in that, Based on effective solids by weight, the joint adhesive comprises: 100 parts of hydroxyl-based waterborne polyurethane, 15-35 parts of carboxylated nitrile latex, 8-20 parts of waterborne epoxy resin, 4-10 parts of water-dispersible polyisocyanate, 0.3-1.5 parts of epoxy silane, 0.2-1.5 parts of silica, 0.05-0.5 parts of silicone defoamer, and 0.05-0.8 parts of rheology modifier.

9. The method for preparing a paper-cloth composite abrasive belt joint according to claim 7, characterized in that, The dry coating amount of the interface conditioning liquid is 2~8 g / m³. 2 The dry coating amount of the joint adhesive is 35~75 g / m. 2 .